Södras gröna skogsbruksplaner ur ett landskapsperspektiv - Alstad, Vibeke (SLU/Southern Swedish Forest Research Centre, 2002)
The aim of the "Green forest management plans" is to help forest owners to reach the environmental goal of the forestry act. But are they able to do that? Is it possible to plan preservation of species on single estates? How do single-estate-plans differ from a landscape analysis and how can the landscape approach be used in operative planning? This work was initiated to give an answer to these questions. This study was made in a landscape of 4200 ha in Östergötland county, south-eastern Sweden. A lanscape analysis was made and then compared to the Green forest management plans in the same area. The nature conservation areas (areas that were set aside to be managed with environmenatl goals) differed quite a lot between the two alternatives. Generally the nature conservation areas were bigger and more coherent in the landscape analysis. The areas that were set aside in the landscape analysis were more limited to certain forest types, the selection was directed towards broadleaves and edges. The nature conservation areas were generally older in the Green forest management plans. The key habitats (identified by the local board of forestry) were set aside in both alternatives. In my opinion the landscape analysis is better, mainly because of the smaller risk of fragmentation. The species depending on the chosen types of biotopes have a great chance to survive. The lanscape approach can be incorporated into the operative planning in different ways, the most important are: 1. To reinforce the keyhabitats and select adjacent areas when possible. 2. To choose the habitats that are important in the actual region. Help and support are given in "Action plan for biodiversity" (made for each region by the Local board of forestry).